Linkages between tree diversity and carbon stocks in unlogged and logged West African tropical forests - Asase, A.; Asitoakor, B.K.; Ekpe, P.K. (International Journal of Biodiversity Science, Ecosystem Services and Management, 2012)
Understanding the long-term effects of logging disturbances on the linkages between tree diversity and carbon stocks is important for conservation efforts and mitigation of global climate change. This study was carried out in unlogged and 14-29 years post-logged forests in the Bia Conservation Area in southwest Ghana. The study results showed that both large (diameter at breast height or dbh10cm) and smaller (dbh10cm but 5cm) tree diversity increased significantly in logged forest compared with unlogged forest while tree dominance was similar between the two land-use types. Tree species guild composition was significantly different due to the higher proportion of pioneer species of large trees in logged forest and shade bearer species of smaller trees in the unlogged forest. Total mean carbon stock was 322.8 Mg C per ha [95% Confidence Interval (CI): 191.6-443.8] for logged forest and 211.2 Mg C per ha (95% CI: 196.9-228.0) for unlogged forest, although no significant difference was detected (p>0.05). There was a significant interaction (p<0.01) between ecological guilds and land use types in total tree-stored carbon stocks. The results of the study showed that logging has comparatively long-term effects on tree diversity while its effect on carbon stocks might only be short term. The findings from this study underscore the need for more comparative data from other areas in West Africa. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: biodiversity; carbon storage; ecosystem services; land use change; logging